The effect of growth regulator on growth rate of amorphopallus titanum - Anggraini, Lia; Mayub, Afrizal; Wardana, Rendy Wikrama; Ruyani, Aceng; Johan, Henny (STKIP Persada Khatulistiwa Sintang, 2025)
The Amorphophallus flower is one of the Endangered species, so there needs to be an effort to preserve breeding with a fast time, namely artificial vegetative. In addition, the a need for a growth hormone to accelerate the growth process so that the number is not extinct, namely growth regulators (ZPT). The purpose of this study was to breed A. titanum vegetatively supported with growth regulators (ZPT) to improve quality and growth rates. The method used is a completely randomized design (CRD), which is divided into 4 treatments namely A (coconut water), B (shallots), C (bamboo shoots), and D (control) with a total of 4 replications so that in this study there were 16 plants (polybags). The results showed that the natural growth regulator treatment of shallot extract gave the best results in the parameter of the number of shoots, while coconut water extract gave the best results in the parameters of shoot length and growth time. Based on the results, it can be concluded that the use of natural growth regulators from coconut water, shallots, and bamboo shoots affects the growth rate of Amorphophallus titanum.